Characterisation of the covalent structure of proteins from biological material by MALDI mass spectrometry ‣ possibilities and limitations. Issue 1 (1998) - Kussmann Kussmann, Martin Martin; Roepstorff Roepstorff, Peter Peter
Abstract : Matrix-assisted laser desorption/ionisation mass spectrometry (MALDI-MS) has become a primary tool for the detailed characterisation of the covalent structure of proteins isolated from biological material, mainly because of its following potentials: high sensitivity and specificity, speed of analysis, appropriateness for mixture analysis, high tolerance towards contaminants, and compatibility with separation techniques, e.g., gel electrophoresis. These characteristics enable the structural analysis of proteins even if they are only available in limited amounts and/or in mixtures, and even if the protein preparations contain large amounts of salts, buffers, detergents and denaturants. Additionally, structural data can be generated within a relatively short time. Whereas X-ray crystallography and multidimensional NMR techniques can provide "absolute" structural data, i.e., a three-dimensional "picture" of the protein of interest, MALDI-MS-especially in combination with selective protein chemistry – yields information on particular aspects of the entire protein structure, e.g., primary structure, active site(s), binding sites, and posttranslational modifications, all of which are often of crucial interest for the understanding of the protein function. Taking into account that protein crystallography and protein NMR studies require large quantities of highly purified sample, MALDI-MS can be even more regarded as a powerful complement in protein structure analysis. This review aims at describing the state-of-the-art of MALDI-MS for characterisation of proteins from biological material by evaluating its potential and limitations.